Screening based approach and dehydrogenation kinetics for MgH2: Guide to find suitable dopant using first-principles approach. Issue 1 (December 2017) - Kumar, E.; Rajkamal, A.; Thapa, Ranjit
Abstract First-principles based calculations are performed to investigate the dehydrogenation kinetics considering doping at various layers of MgH2 (110) surface. Doping at first and second layer of MgH2 (110) has a significant role in lowering the H2 desorption (from surface) barrier energy, whereas the doping at third layer has no impact on the barrier energy. Molecular dynamics calculations are also performed to check the bonding strength, clusterization, and system stability. We study in details about the influence of doping on dehydrogenation, considering the screening factors such as formation enthalpy, bulk modulus, and gravimetric density. Screening based approach assist in finding Al and Sc as the best possible dopant in lowering of desorption temperature, while preserving similar gravimetric density and Bulk modulus as of pure MgH2 system. The electron localization function plot and population analysis illustrate that the bond between Dopant-Hydrogen is mainly covalent, which weaken the Mg-Hydrogen bonds. Overall we observed that Al as dopant is suitable and surface doping can help in lowering the desorption temperature. So layer dependent doping studies can help to find the best possible reversible hydride based hydrogen storage materials.